Molecular and Mechanistic Characterization of PddB, the First PLP-Independent 2,4-Diaminobutyric Acid Racemase Discovered in an Actinobacterial D-Amino Acid Homopolymer Biosynthesis - Yamanaka, Kazuya; Ozaki, Ryo; Hamano, Yoshimitsu; Oikawa, Tadao (Frontiers in Microbiology, 2021)
We recently disclosed that the biosynthesis of antiviral γ-poly-D-2,4-diaminobutyric acid (poly-D-Dab) in Streptoalloteichus hindustanus involves an unprecedented cofactor independent stereoinversion of Dab catalyzed by PddB, which shows weak homology to diaminopimerate epimerase (DapF). Enzymological properties and mechanistic details of this enzyme, however, had remained to be elucidated. Here, through a series of biochemical characterizations, structural modeling, and site-directed mutageneses, we fully illustrate this novel Dab-specific PLP-independent racemase PddB and further provide an insight into its evolution. The activity of the recombinant PddB was shown to be optimal around pH 8.5, and its other fundamental properties resembled those of typical PLP-independent racemases/epimerases. The enzyme catalyzed Dab specific stereoinversion with a calculated equilibrium constant of nearly unity, demonstrating that the reaction catalyzed by PddB is indeed racemization. Its activity was inhibited upon incubation with sulfhydryl reagents, and the site-directed substitution of two putative catalytic Cys residues led to the abolishment of the activity. These observations provided critical evidence that PddB employs the thiolate-thiol pair to catalyze interconversion of Dab isomers. Despite the low levels of sequence similarity, a phylogenetic analysis of PddB indicated its particular relevance to DapF among PLP-independent racemases/epimerases. Secondary structure prediction and 3D structural modeling of PddB revealed its remarkable conformational analogy to DapF. Further, PddB homologs which seemed to be narrowly distributed only in actinobacterial kingdom were constantly encoded adjacent to the putative poly-D-Dab synthetase gene. These observations strongly suggested that PddB could have evolved from the primary metabolic DapF in order to organize the biosynthesis pathway for the particular secondary metabolite, poly-D-Dab. The present study is on the first molecular characterization of PLP-independent Dab racemase and provides insights that could contribute to further discovery of unprecedented PLP-independent racemases.